The impact of the endometrial microbiome on IVF outcomes – current evidence - Malczyk, Anna; Zienkiewicz, Damian; Makulec, Gabriela; Domosud, Karolina; Walendziak, Weronika; Mordal, Natalia; Ściebura, Kacper; Wiśniewska, Wiktoria; Ostaszewska, Magdalena; Majchrzyk, Milena (Journal of Education, Health and Sport, 2026)
Background: The uterine cavity, previously considered as an aseptic physiological milieu is now recognized as host to a distinct endometrial microbial community (EM). This analysis aims to elucidate the influence of the EM taxonomic configuration on female reproductive morbidity, with particular emphasis on its implications for Recurrent Implantation Failure (RIF). Furthermore, the study assesses the prognostic value of the EM profile in determining clinical outcomes following Assisted Reproductive Technologies (ART), specifically In Vitro Fertilization (IVF). Aim: This systematic review was designed to elucidate the correlation between the metagenomic composition of the endometrial microbiome and female infertility. Material and methods: The methodology centered on the comprehensive identification and rigorous critical appraisal of clinical evidence archived within the PubMed/ MEDLINE and the Cochrane Library. Summary: The presence of a eubiotic Lactobacillus-dominated (LD) endometrial microbiome (EM) is highly correlated with optimized endometrial receptivity and subsequently elevated rates of successful implantation, continuation of pregnancy, and live birth following assisted reproductive technology (ART) procedures. Conversely, an endometrial dysbiotic state, often characterized as non-Lactobacillus-dominated (non-LD) EM, is consistently associated with a substantial reduction in reproductive success. Studies of patients with recurrent implantation failure (RIF) identified a significantly higher relative abundance of various pathogenic bacterial genera in the EM compared with control subjects. Although the endometrial abundance of Lactobacillus did not differ significantly between women with RIF and control subjects, reduced vaginal Lactobacillus rates in the RIF group compared to controls suggest that vaginal concentrations may represent a potential biomarker for RIF.